Ore Characteristics and Fluid Inclusion of the Base Metal Vein Deposit in Moncong Bincanai Area, Gowa, South Sulawesi, Indonesia - Asmariyadi Asmariyadi; R. Langkoke; A. Maulana; I. Nur; W. AstamAn (Indonesian Journal on Geoscience, 2012)
DOI: 10.17014/ijog.v7i4.146This paper is dealing with ore characteristics and fluid inclusion of the Moncong Bincanai, Biringbulu Subregency of Gowa Regency, South Sulawesi Province, Indonesia. The mineralization is a vein type, with the orientation of N170oE /65oSW, hosted in open-space filling within basalt. The mineralization consists of galena, sphalerite, chalcopyrite, and pyrite. Vein thickness ranges from 5 - 17 cm, showing a crustiform banding texture, with a sequence from outer to centre: quartz, carbonate (siderite), sulphide. The quartz displays primary growth textures such as comb, crystalline, saccharoidal, and colloform. Analytical methods applied include AAS and fluid inclusion microthermometry. Chemical composition of the vein indicates an average of Pb = 47.92%, Cu = 1.27%, Zn = 1.02%, and Fe = 9.46%, which shows a significant concentration of Pb. Fluid inclusion microthermometry results indicate a range of formation temperature of 240 - 250C and salinity of the responsible hydrothermal fluid of 2.1 - 2.5 wt.% NaCl eq. The deposit is categorized into low-sulfidation epithermal deposits, which was formed within a range of 410 - 440 m below paleosurface.